Workplace spirituality as a moderator in relation between stress and health: An exploratory empirical assessment. (June 2014) - Kumar, Vineet; Kumar, Sandeep
Abstract The present study explores the role of workplace spirituality in moderating the relationship between occupational stress and the health of managerial personnel in India. A sample of 150 managers working in different public and private organizations was used to measure workplace spirituality, occupational stress, and health using the Spirituality at Work scale, the Occupational Stress Index and the 28-item General Health Questionnaire, respectively. The findings reveal that workplace spirituality moderates the negative relationship of stress and health. The study also found that stress has a negative impact on health while workplace spirituality positively correlated with health. The findings also support the practical importance of spirituality in the workplace for improving health conditions by providing a healthy atmosphere and meaningful work for employees. This exploratory study encourages future research to understand the role of spirituality in the workplace.